Flow Diversion for the Treatment of Basilar Apex Aneurysms. Issue 6 (26th February 2018) - Dmytriw, Adam A; Adeeb, Nimer; Kumar, Ashish; Griessenauer, Christoph J; Phan, Kevin; Ogilvy, Christopher S; Foreman, Paul M; Shallwani, Hussain; Limbucci, Nicola; Mangiafico, Salvatore; Michelozzi, Caterina; Krings, Timo; et al.
Abstract: BACKGROUND: Flow diversion for basilar apex aneurysms has rarely been reported. OBJECTIVE: To assess flow diversion for basilar apex aneurysms in a multicenter cohort. METHODS: Retrospective review of prospectively maintained databases at 8 academic institutions was performed from 2009 to 2016 to identify patients with basilar apex aneurysms treated with flow diversion. Clinical and radiographic data were analyzed. RESULTS: Sixteen consecutive patients (median age 54.5 yr) underwent 18 procedures to treat 16 basilar apex aneurysms with either the Pipeline Embolization Device (Medtronic Inc, Dublin, Ireland) or Flow Redirection Endoluminal Device (Microvention, Tustin, California). Five aneurysms (31.3%) were treated in the setting of subarachnoid hemorrhage. Seven aneurysms (43.8%) were treated with flow diversion alone, while 9 (56.2%) underwent flow diversion and adjunctive coiling. At a median follow-up of 6 mo, complete (100%) and near-complete (90%-99%) occlusion was noted in 11 (68.8%) aneurysms. Incomplete occlusion occurred more commonly in patients treated with flow diversion alone compared to those with adjunctive coiling. Patients with partial occlusion were significantly younger. Retreatment with an additional flow diverter and adjunctive coiling occurred in 2 aneurysms with wide necks. There was 1 mortality in a patient (6.3%) who experienced posterior cerebral artery and cerebellar strokes as well as subarachnoid hemorrhage after the placement of a flow diverter. Minor complications occurred in 2 patients (12.5%). CONCLUSION: Flow diversion for the treatment of basilar apex aneurysms results in acceptable occlusion rates in highly selected cases. Both primary flow diversion and rescue after failed clipping or coiling resulted in a modified Rankin Scale score that was either equal or better than at presentation and the technology represents a viable alternative or adjunctive option.